PENGARUH PENGGUNAAN SISTEM ADMINISTRASI e-REGISTRATION, e- BILLING, e-SPT, DAN e-FILLING TERHADAP KEPATUHAN WAJIB PAJAK (Studi Pada Wajib Pajak Orang Pribadi Di RSUD Dr. Moewardi Surakarta) - Murniati Sulistyorini; Siti Nurlaela; Yuli Chomsatu S (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study was conducted to determine the effect of the administrative system of e-Registration, ebilling, e-SPT, and e-Filling the individual taxpayer compliance in hospitals Dr. Moewardi Surakarta. Respondents in this study are the personal taxpayer (employee) in hospitals. Dr. Moewardi Surakarta. Source data used are primary data through a questionnaire survey method.The sampling technique used purposive sampling method with a sample of 66 respondents.Methods of data analysis using multiple linear regression test. These results indicate that: 1) Use of the administrative system of e-Registration effect on tax compliance, 2) Use of the administrative system of e-Billing influence on tax compliance, 3) Use of the administrative system of e-SPT effect on tax compliance, 4) the use of e-administration system Filling effect on tax compliance.Keywords: Use of e-Registration System Administration, e-billing, e-SPT, e-Filling, tax complianc